2016
DOI: 10.1089/cbr.2016.2034
|View full text |Cite
|
Sign up to set email alerts
|

Interfering EZH2 Expression Reverses the Cisplatin Resistance in Human Ovarian Cancer by Inhibiting Autophagy

Abstract: We aimed to determine the effects of the inhibition of enhancer of zeste homolog 2 (EZH2) gene expression on the cisplatin resistance of the human ovarian cancer cell line, SKOV3/DDP, and to identify the underlying mechanisms. SKOV3/DDP cells were stably transfected with pSUPER-EZH2 (EZH2 RNA interference plasmid) or pcDNA3.1-EZH2 (EZH2 gene overexpression plasmid) using the lipofection method. Real-time fluorescence quantitative reverse transcription polymerase chain reaction and western blotting confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Patients with ovarian cancer usually respond well to initial chemotherapy with cisplatin. However, most patients develop resistance to cisplatin during the course of their treatment ( 1 , 19 ). Hence, there is an urgent need to identify new therapeutic targets in ovarian cancer and to develop novel, potent and specific drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ovarian cancer usually respond well to initial chemotherapy with cisplatin. However, most patients develop resistance to cisplatin during the course of their treatment ( 1 , 19 ). Hence, there is an urgent need to identify new therapeutic targets in ovarian cancer and to develop novel, potent and specific drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of miR-31 on the efficacy of platinum compounds have been discussed extensively. It has been shown that the expression levels of miR-31 are negatively correlated with E2F transcription factor 2 (E2F2) and Enhancer of zeste homolog 2 (EZH2) in malignant tumors including gastric, ovarian and bladder cancer, and CRC (37)(38)(39)(40)(41). E2F2 and EZH2 can enhance drug resistance by inhibiting platinum-drug-mediated apoptosis, whereas low expression levels of E2F2 and EZH2 enhance platinum chemosensitivity (39,(42)(43)(44)(45).…”
Section: Os ---------------------------------------------------------mentioning
confidence: 99%
“…Overexpressed PDA/PD-L1 not only decreased immunotherapy efficiency, but also increased lung cancer resistance to cisplatin [ 12 ]. In human ovarian cancer, upregulated zeste homolog 2 (EZH2) resulted in cisplatin by promoting cyclin-dependent kinases (CDK1, CDK2) and H3K27me3 [ 13 ]. In bladder cancer cells, the long non-coding RNA UCA1 increased cisplatin resistance by promoting microRNA (miR)-196a-5p expression targeting p27 kip1 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%